IMPLEMENTATION OF DIGITAL ENGLISH LEARNING TOWARD JUNIOR HIGH SCHOOL STUDENTS BASED ON MERDEKA CURRICULUM - Putra, Octa Pratama (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
The purpose of this study is to peer out the results of the final perspective of Hidayatul Athfal junior high schools’ students in implementing digital English learning which refers to Merdeka curriculum. Beforehand, the Ministry of Education issued one of the latest efforts to change the education system, which is popularly known as the Merdeka curriculum. Based on the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System, curriculum is a set of plans and arrangements regarding objectives, content, and teaching materials, as well as methods used as guidelines for implementing up-to-date learning to achieve effective and optimal learning objectives. Apart from that, junior high school students in this research used learning media, it is barcode scanners as one of the learning media to make the digital system of the learning process at their meetings. The author uses a qualitative descriptive research method, which is conducted by direct observation and in-depth interviews with the parties involved, and the data collected is then analyzed descriptively by presenting the results of the research in the form of a research report. The conclusion of the research that the author draws that, it shows the implementation of the Merdeka curriculum is very helpful in assisting the junior high school students by adapting digital English learning process. It is proved that, 66.7% of students agreed with the implementation of the Merdeka Curriculum.